Environmental degradation of structural materials in liquid lead- and lead-bismuth eutectic-cooled reactors. (May 2022) - Gong, Xing; Short, Michael P.; Auger, Thierry; Charalampopoulou, Evangelia; Lambrinou, Konstantina
Abstract: Liquid lead (Pb)- and lead–bismuth eutectic (LBE)-cooled fast neutron reactors (Gen-IV LFRs) are one of the most technologically mature fission reactor technologies, due to their inherent safety, high power density, and ability to burn nuclear waste. Accelerator-driven systems (ADS), in particular, promise to address the issues of long-lived radiotoxic nuclear waste, emerging uranium ore shortages, and the ever-increasing demand for energy. However, the conditional compatibility of conventional structural materials, such as steels, with liquid Pb and liquid LBE is still an important concern for the deployment of these advanced nuclear reactor systems, making the environmental degradation of candidate structural and fuel cladding steels the main impediment to the construction of Gen-IV LFRs, including ADS. This article presents a comprehensive review of the current understanding of environmental degradation of materials in contact with liquid Pb and liquid LBE, with a focus on the underlying mechanisms and the factors affecting liquid metal corrosion (LMC) and liquid metal embrittlement (LME), which are the two most important materials degradation effects. Moreover, this article addresses the most promising LMC and LME mitigation approaches, which aim to suppress their adverse influence on materials performance. An outlook of the needed future work in this field is also provided.